Pendampingan Pemanfaatan Gamifikasi untuk Pendidikan di Masa Depan (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2022)
One of the strategies of Information Technology in the field of learning is using the game method to develop learning methods. Learning is the main activity of the educational process in schools which aims to produce behavioral changes. The use of gamification in learning requires strategies in using it such as game mechanics, aesthetics, and game thinking to involve people, provide encouragement and motivation, and learn to solve problems. The results of the analysis carried out on the literature review provide an overview of the four gamification-based tools used, each of which has advantages and disadvantages. Assistance and utilization of gamification tools in supporting the learning process carried out at SDN Semangat Bakti can be carried out according to learning needs. Assistance in the use of gamification for education in the future needs to be carried out to prepare the next generation of the nation so that the learning process can adapt to the development of information and communication technology.